The CRI v2.2 reduced degradation scheme for isoprene. (1st September 2019) - Jenkin, M.E.; Khan, M.A.H.; Shallcross, D.E.; Bergström, R.; Simpson, D.; Murphy, K.L.C.; Rickard, A.R.
Abstract: The reduced representation of isoprene degradation in the Common Representative Intermediates (CRI) mechanism has been systematically updated, using the Master Chemical Mechanism (MCM v3.3.1) as a reference benchmark, with the updated mechanism being released as CRI v2.2. The complete isoprene degradation mechanism in CRI v2.2 consists of 186 reactions of 56 closed shell and free radical species, this being an order of magnitude reduction in size compared with MCM v3.3.1. The chemistry initiated by reaction with OH radicals, NO3 radicals and ozone (O3 ) is treated. An overview of the updates is provided, within the context of reported kinetic and mechanistic information. The revisions mainly relate to the OH-initiated chemistry, which tends to dominate under atmospheric conditions, although these include updates to the chemistry of products that are also generated from the O3 - and NO3 -initiated oxidation. The revisions have impacts in a number of key areas, including recycling of HOx and NOx . The performance of the CRI v2.2 isoprene mechanism has been compared with those of the preceding version (CRI v2.1) and the reference MCM v3.3.1 over a range of relevant conditions, using a box model of the tropical forested boundary layer. In addition, tests are carried out to ensure that the performance of MCM v3.3.1 remains robust to more recently reported information. CRI v2.2 has also been implemented into the STOCHEM chemistry-transport model, with a customized close-variant of CRI v2.2 implemented into the EMEP MSC-W chemistry-transport model. The results of these studies are presented and used to illustrate the global-scale impacts of the mechanistic updates on HOx radical concentrations. Highlights: Isoprene chemistry in a reduced (lumped chemistry) scheme is updated. Detailed MCM v3.3.1 isoprene chemistry is used as a reference benchmark. An order of magnitude reduction in species and reaction numbers is achieved. Performance of MCM v3.3.1 is tested in relation to recently reported information. Impacts of updates on global-scale [HOx ] are illustrated using two global models.